Botryoidal and Spherulitic Aragonite in Carbonates Associated with Microbial Mats: Precipitation or Diagenetic Replacement Product? - Ge, Yuzhu; Della Porta, Giovanna; Pederson, Chelsea L.; Lokier, Stephen W.; Hoffmann, René; Immenhauser, Adrian (Frontiers in Earth Science, 2021)
Similar carbonate fabrics may result from different pathways of precipitation and diagenetic replacement. Distinguishing the underlying mechanisms leading to a given carbonate fabric is relevant, both in terms of an environmental and diagenetic interpretation. Prominent among carbonate fabrics are aragonite botryoids and spherulites, typically interpreted as direct seawater precipitates and used as proxies for fluid properties and depositional environments. This study investigated μm to mm-scale Holocene botryoidal and spherulitic aragonite from marine and non-marine carbonate settings associated with microbial mats, and reports two distinct formation mechanisms: 1) early diagenetic replacement, and 2) primary precipitation via nanocrystal aggregation. In the intertidal microbial mats of Khawr Qantur (Abu Dhabi), botryoidal and spherulitic aragonite are replacement products of heavily micritized bioclasts. To form the botryoidal and spherulitic aragonite, skeletal rods and needles, resulting from disintegration of micritized bioclasts, recrystallize into nanocrystals during early marine diagenesis. These nanocrystals then grow into fibrous crystals, forming botryoidal and spherulitic aragonite. In the lacustrine microbial bioherms of the hypersaline Great Salt Lake (United States) and in the hydrothermal travertines of Bagni San Filippo (Italy), botryoidal and spherulitic aragonite evolve from nanocrystals via precipitation. The nanocrystals are closely associated with extracellular polymeric substances in microbial biofilms and aggregate to form fibrous crystals of botryoidal and spherulitic aragonite. The studied fabrics form a portion of the bulk sediment and show differences in terms of their formation processes and petrological features compared to the often larger (few mm to over 1 m) botryoidal and spherulitic aragonite described from open-marine reefal cavities. Features shown here may represent modern analogues for ancient examples of carbonate depositional environments associated with microbialites. The implication of this research is that botryoidal and spherulitic aragonite associated with microbial mats are relevant in paleoenvironmental interpretations, but must be combined with a detailed evaluation of their formation process. Care must be taken as the term “botryoidal and spherulitic aragonite” may in fact include, from the viewpoint of their nucleation and formation mechanism, similar fabrics originated from different pathways. At present, it seems unclear to which degree the μm to mm-scale botryoids and spherulites described here are comparable to their cm-to dm-size counterparts precipitated as cements in the open pore space of reefal environments. However, it is clear that the investigation of ancient botryoidal and spherulitic aragonite must consider the possibility of an early diagenetic replacement origin of these precipitates.